2005
DOI: 10.1523/jneurosci.0693-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Self-Motion and the Hippocampal Spatial Metric

Abstract: Self-motion signals are sufficient for animal navigation ("path integration") and for updating hippocampal location-specific firing. The contributions of ambulatory, vestibular, and optic self-motion signals to CA1 unit activity and EEG were studied while rats either walked or drove a car between locations on a circular track (referred to as WALK and CAR, respectively) or experienced pseudomotion, in which the animal was stationary and the environment was rotated (WORLD). Fewer pyramidal cells expressed place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
178
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(191 citation statements)
references
References 43 publications
11
178
2
Order By: Relevance
“…By contrast, no species may need grids larger than a few meters because grid maps are likely to be local and fragmented in all realistic environments 98 . An important point to note, however, is that humans are obviously not locomoting during fMRI scanning, and this might influence the scale of the place fields during scanning, similar to what has been observed in rodents locomoting by train instead of walking themselves 99 . Studies in monkeys have also been limited for practical reasons: thus far these have involved head fixation 94 .…”
Section: Spatial Processing In Primatesmentioning
confidence: 89%
“…By contrast, no species may need grids larger than a few meters because grid maps are likely to be local and fragmented in all realistic environments 98 . An important point to note, however, is that humans are obviously not locomoting during fMRI scanning, and this might influence the scale of the place fields during scanning, similar to what has been observed in rodents locomoting by train instead of walking themselves 99 . Studies in monkeys have also been limited for practical reasons: thus far these have involved head fixation 94 .…”
Section: Spatial Processing In Primatesmentioning
confidence: 89%
“…Previous experiments have shown that the phase precession slope of place cells correlated with the size of its place field (7,19,28) so that the total phase precession is always about one full cycle, and that both the phase precession slope and field size increase along the septotemporal axis of the hippocampus (29). It has been suggested that phase precession can be produced by faster oscillating pyramidal cells than the LFP, and it has been shown that the phase-space relationship is speed-independent (2), but no mechanisms were provided.…”
Section: Speed-dependent Oscillation Of Place Cells Can Keep the Spikmentioning
confidence: 99%
“…Interestingly, when some self-generated movement information is eliminated, e.g., by moving a rat passively in the environment, place fields are larger than when a rat is actively moving in the same environment [24]. Similarly, when the environment is rotated around a stationary rat, and thus only the movement of distal visual objects suggests movement, the spatial information content per spike of place cells is reduced by 50% [25]; i.e., an experiment similar to virtual reality, or the experience one can have when sitting in a stationary train, watching an adjacent departing train. Thus, altogether these experiments indicate that the ensemble of spatial information derived from different sensory modalities contributes to the selectivity of place cells firing, and that the highest selectivity is obtained when all sources of spatial information are coherent, as is normally the case in the real world.…”
Section: As the World Turns: A Neurobiological Perspectivementioning
confidence: 99%